Measuring the impact of digital transformation on companies' productivity, efficiency, and competitiveness - Mohamed Gaber Qasim Al-Sharqawi, (International Journal of Computers and Informatics, 2025)
Digital transformation tools have become a fundamental pillar upon which companies rely to enhance their performance and increase their competitiveness. This study aims to explore the impact of these tools on corporate productivity and efficiency, asking how digital technology applications impact overall organizational performance. The results showed that the use of digital transformation tools significantly contributes to improving productivity within companies. For example, cloud systems have improved access to data and facilitated collaboration between teams, while data analytics and artificial intelligence tools have enhanced decision-making by providing accurate and reliable insights. Improvements in operational efficiency were also observed, as digital tools have helped reduce human errors and expedite procedures. Several challenges that companies may face when implementing digital transformation were also identified. These challenges include resistance to change among some employees, high costs of technology investment and maintenance, and difficulties in integrating digital tools with legacy systems. These challenges require special attention to ensure the successful implementation of digital strategies. The study provides practical recommendations for companies, including developing clear strategies for adopting digital transformation tools, investing in employee training, and fostering a technology-supportive organizational culture. It also calls on researchers to conduct further studies to explore the impact of digital tools across different industrial sectors and at different levels of companies. The study highlights the importance of integrating digital transformation tools into corporate strategies to improve overall performance and increase productivity and efficiency. Its findings contribute to a deeper understanding of the actual impact of digital technology on companies, helping them refine their strategies and increase their competitiveness in the market.
Keywords: Digital transformation; productivity; efficiency; competitiveness